2007
DOI: 10.2304/rcie.2007.2.1.29
|View full text |Cite
|
Sign up to set email alerts
|

The Digital Literacy of Seniors

Abstract: This article describes national and international comparative quantitative and qualitative empirical results for media use and media behaviour of elderly people against the background of demographic change and development in the sphere of information technology. Besides gender, professional position and educational qualification, age and affiliation to a generation are -in terms of 'country', origin or culture -the most significant predictors of whether someone is familiar with the computer and the Internet an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 14 publications
(4 reference statements)
2
20
0
Order By: Relevance
“…This results in a troubling conclusion: not only does the elderly population in Western countries have less access to technology than younger adults, but even those with access have less digital skills, and make more limited use of the technology they do have. This conclusion mirrors results from studies on digital literacy which have found that the elderly often have lower levels of skilled, competent use of technology in their daily lives ( 70 , 71 ).…”
Section: The Digital Dividesupporting
confidence: 81%
“…This results in a troubling conclusion: not only does the elderly population in Western countries have less access to technology than younger adults, but even those with access have less digital skills, and make more limited use of the technology they do have. This conclusion mirrors results from studies on digital literacy which have found that the elderly often have lower levels of skilled, competent use of technology in their daily lives ( 70 , 71 ).…”
Section: The Digital Dividesupporting
confidence: 81%
“…As a volunteer expressed, for some users and volunteers, being able to follow familiar cultural practices, such as sitting in a rocking chair, singing, and having coffee together via the VC service, supported the domestication of technology (Lie & Sørensen, 1996;Silverstone & Haddon, 1996). Furthermore, older people's use of new media may be influenced by their previous media-related practices and experiences (Schäffer, 2007). This was evident in our findings.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, there are significantly more Internet non-users among older than among younger age groups (Ofcom, 2019a;Rasi, 2018). Echoing the life course perspective presented earlier in this editorial article, Schäffer (2007) demonstrated that older people's use of new technologies is influenced by their accumulating experiences. Schäffer studied the media practice cultures of older people and concluded that "they initially approach new technologies by applying the media practices they picked up during adolescence, including the logic inherent in these practices" (p. 36).…”
Section: Older Peoplementioning
confidence: 83%
“…In her study, she applies the theory of sensemaking (Weick, 1995) to shed light on the viewpoints and experiences of older adults living in sparsely populated areas in Finland and receiving technological home care services. In the spirit of the life course approach presented in the previous sections, she emphasizes that digitalizing care service is not a straightforward procedure, as the use or rejection of technologies is intertwined with older people's past experiences (see also Schäffer, 2007) as well as social, structural, and political issues. She concludes that media literacy education initiatives aimed toward older people should be based on careful contextualization, and that older people's voices should be considered and heard in the design of initiatives and in public discussions.…”
Section: Older Peoplementioning
confidence: 99%